2013
DOI: 10.1016/j.saa.2013.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy of the phosphate mineral lazulite – (Mg, Fe)Al2(PO4)2·(OH)2 found in the Minas Gerais, Brazil

Abstract: This research was done on lazulite samples from the Gentil mine, a lithium bearing pegmatite located in the municipality of Mendes Pimentel, Minas Gerais, Brazil. Chemical analysis was carried out by electron microprobe analysis and indicated a magnesium rich phase with partial substitution of iron. Traces of Ca and Mn, (which partially replaced Mg) were found. The calculated chemical formula of the studied sample is: (Mg0.88, Fe0.11)Al1.87(PO4)2.08(OH)2.02. The Raman spectrum of lazulite is dominated by an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 17 publications
0
18
1
3
Order By: Relevance
“…The H-bonding scheme in the structure of lazulite here described is compatible with the findings based on infrared and Raman spectroscopies (e.g., Frost et al 2013, RRUFF database: http://rruff.info/Lazulite), as IR and Raman spectra, in the region of the OH stretching active modes, show evidence of more than one unique H-bond. The description of the IR and Raman mode in lazulite provided by Frost et al (2013) is likely affected by misinterpretation: the structure does not contain HPO 4 or H 2 PO 4 units, and, in addition, the conclusion "The proton on the hydroxyl units is apparently very mobile and enables the formation of the monohydrogen and dihydrogen phosphate units" (Frost et al 2013) is inconsistent with our experimental findings and, in general, not plausible. We expect that a more robust description of the active IR and Raman vibrational modes will be delivered on the basis of the structure models of this study.…”
Section: Resultscontrasting
confidence: 81%
See 3 more Smart Citations
“…The H-bonding scheme in the structure of lazulite here described is compatible with the findings based on infrared and Raman spectroscopies (e.g., Frost et al 2013, RRUFF database: http://rruff.info/Lazulite), as IR and Raman spectra, in the region of the OH stretching active modes, show evidence of more than one unique H-bond. The description of the IR and Raman mode in lazulite provided by Frost et al (2013) is likely affected by misinterpretation: the structure does not contain HPO 4 or H 2 PO 4 units, and, in addition, the conclusion "The proton on the hydroxyl units is apparently very mobile and enables the formation of the monohydrogen and dihydrogen phosphate units" (Frost et al 2013) is inconsistent with our experimental findings and, in general, not plausible. We expect that a more robust description of the active IR and Raman vibrational modes will be delivered on the basis of the structure models of this study.…”
Section: Resultscontrasting
confidence: 81%
“…1). However, in a more recent paper, based on infrared and Raman investigations of lazulite, Frost et al (2013) reported evidence of bending modes ascribed to tetrahedral PO 4 , HPO 4 and H 2 PO 4 units. These experimental findings are not consistent with the structural model reported by Lindberg and Christ (1959) and Giuseppetti and Tadini (1983), in which HPO 4 and H 2 PO 4 groups are supposed not to occur.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…1394.31 cm -1 could be associated with MF because the same peak was also observed on pure MF spectrum. Peak 1066.28 cm -1 belongs to PO4 3-antisymmetric stretching frequency [37][38][39][40][41][42][43], 117267 cm -1 and 1052.22 cm -1 were also assigned to PO4 3antisymmetric stretching movement [44]. According to literature, Breitinger and co-workers emphasized that the deceptively simple strong vibrations centered at 1059 cm -1 including minimum four components of inorganic phosphate (PO4), were produced by removal of the threefold degeneracy of PO4 and activation of the general mode of phosphate (PO4) [44].…”
Section: Ftir Analysismentioning
confidence: 99%